2018
DOI: 10.20546/ijcmas.2018.711.410
|View full text |Cite
|
Sign up to set email alerts
|

Soil Organic Carbon Fractions, Soil Microbial Biomass Carbon, and Enzyme Activities Impacted by Crop Rotational Diversity and Conservation Tillage in North West IGP: A Review

Abstract: Soil organic carbon (SOC) and its fractions (labile and non-labile) including particulate organic carbon (POC) and its components [coarse POC and fine POC], light fraction organic carbon (LFOC), readily oxidizable organic carbon, dissolved organic carbon (DOC) are important for sustainability of any agricultural production system as they govern most of the soil properties, and hence soil quality and health. Being a food source for soil microorganisms, they also affect microbial activity, diversity and enzymes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…This might be due to the reason that conservation agriculture had improved soil properties, better crop establishment and minimum lodging. Similar results were reported by Jat et al (2017) and Chaudhary et al (2018). Although, harvest index was higher in ZT-ZTR in maize and CT-ZT in wheat crop.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This might be due to the reason that conservation agriculture had improved soil properties, better crop establishment and minimum lodging. Similar results were reported by Jat et al (2017) and Chaudhary et al (2018). Although, harvest index was higher in ZT-ZTR in maize and CT-ZT in wheat crop.…”
Section: Discussionsupporting
confidence: 91%
“…Other major problems like imbalance use of pesticides, nutrients deficiencies or imbalances, high energy and labour requirement and weed shift cause threat to the sustainability of cereals based cropping system (Pathak et al, 2011;Ram et al, 2012). Many studies have shown that continuous no-tillage for long term increases soil organic matter (Bhattacharyya et al, 2009;, soil health, improve soil structure (Jat et al, 2018) and increases crop yield substantially than intensive tillage practices (Cannell and Hawes, 1994). Therefore, conservation strategies and modern farming techniques must be incorporated in the indigenous production systems for environmental protection, economic and social development and ecologically sustainability (Singh and Rao, 2002).Therefore, an experiment on maizewheat cropping sequence was conducted to study the effect of tillage in relation to weed management on crop DMA, growth indices and biological yield in the North-Western Himalayas.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al (2016) revealed that MBC concentration was significantly higher under zero tillage treatments. Acid phosphatase activity was greater under zero tillage than under conventionally plowed plots with a disk harrow and disk plow (Chaudhary et al 2018). Results from the present study showed that on a short-term basis, soil microbial dynamics and activities are highly influenced by the method and degree of tillage practices along with either incorporation of residue is done or not and different tactics of weed management used in maize wheat cropping system.…”
Section: Resultsmentioning
confidence: 62%